Autofiction : A Female Francophone Aesthetic of Exile. - Wimbush, Antonia, 1989- (Liverpool University Press, 2021)
This book examines themes of exile, mobility, and identity in contemporary autofictional narratives written in French by women writers from across the francophone world. It reads exile in light of both gender and literary genre, arguing that autofiction gives women the space to reconfigure their exile on their own terms.
Description based upon print version of record.
Keywords: Autobiographical fiction, French -- History and criticism.; Autobiographical fiction -- Women authors.; Exiles in literature.; Social mobility in literature.; Mobilité sociale dans la littérature.; LITERARY CRITICISM / Women Authors; Autobiographical fiction, French; Exiles in literature; Social mobility in literature; Exile; Autofiction; Women's writing; Postcolonial; Gender; Criticism, interpretation, etc.